SEMARANG CITY HOUSING INFRASTRUCTURE MANAGEMENT BASED ON REGIONAL REGULATION AND MAYOR REGULATION - Kun Fadira Fachrani; Zil Aidi (Awang Long Law Review, 2023)
The provision of infrastructure governance is often the center of attention for problems in residential areas because infrastructure services are not fulfilled. Communities should be able to feel these services for free in their housing environment. This writing aims to identify and analyze the duties and functions of the Housing and Settlement Area Department (Disperkim) in providing quality infrastructure for communities in residential areas. Researchers used legal research methods with a normative juridical approach. The results of this study indicate the duties and functions of the Housing and Settlement Area Department as one of the Regional Apparatuses or Regional Technical Implementation Units of the City of Semarang in improving the quality of housing and settlement infrastructure.